2010
DOI: 10.1258/ijsa.2009.008505
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of research-related HIV testing programmes contribute to detection of more HIV infections

Abstract: HIV prevalence estimates from bathhouse testing programmes differ widely, ranging from 3% to 11%. The observed difference may be a consequence of whether the programme was part of a research project or a community-based programme. A research-funded testing programme was offered at a bathhouse between May 2001 and December 2002. A local community-based organization began a testing programme in July 2006 at the same bathhouse; the data for this analysis cover the period July 2006 through December 2007. County-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These results are not intended to assess that primary purpose, and the lack of a robust effect on sexual risk behavior inside the bathhouse should not be considered a reason to drop or reduce the presence of these programs at bathhouses. Even if the effect on UAI is minimal, it is still likely that these programs meet their primary aims, as a number of other studies have shown (Bingham et al, 2008; Daskalakis et al, 2009; Huebner et al, 2010; Huebner et al, 2006; Spielberg et al, 2005; Woods et al, 2010a). Moreover, it should be noted that in a bathhouse serving a large metropolitan area (particularly one that never closes), the yearly clientele can number in the tens of thousands, so even the modest reduction in sexual risk behavior suggested by this analysis may prevent thousands of potential risk events annually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are not intended to assess that primary purpose, and the lack of a robust effect on sexual risk behavior inside the bathhouse should not be considered a reason to drop or reduce the presence of these programs at bathhouses. Even if the effect on UAI is minimal, it is still likely that these programs meet their primary aims, as a number of other studies have shown (Bingham et al, 2008; Daskalakis et al, 2009; Huebner et al, 2010; Huebner et al, 2006; Spielberg et al, 2005; Woods et al, 2010a). Moreover, it should be noted that in a bathhouse serving a large metropolitan area (particularly one that never closes), the yearly clientele can number in the tens of thousands, so even the modest reduction in sexual risk behavior suggested by this analysis may prevent thousands of potential risk events annually.…”
Section: Discussionmentioning
confidence: 99%
“…On-site testing has shown demonstrable value by revealing unidentified infections and reaching populations of men who might not otherwise test (Bingham et al, 2008; Daskalakis et al, 2009; Huebner et al, 2010; Huebner et al, 2006; Mayer et al, 2011; Spielberg et al, 2005; Woods et al, 2010a). In addition, such programs coincide with the “National HIV/AIDS Strategy for the United States” (2010) because they bring HIV screening and surveillance to a subgroup of MSM who are at even higher risk for HIV transmission and target unidentified infections (Collins & Diallo, 2010; Millett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has focused on the challenges of implementing HIV testing programs in clubs,12-15 while other studies have shown that men at clubs will avail themselves of testing when it is available on site7,16-18 and that such in-club testing has been associated with reduced risk behavior over a 3-month period 19,20. The scientific literature indicates a wide range of HIV prevention programs, and services have been initiated in clubs to try to reach men at risk with important HIV prevention services and information 4,7,14,16-21. In order to determine the extent to which HIV prevention is implemented in clubs across the United States, we interviewed club managers.…”
Section: Introductionmentioning
confidence: 99%